TINJAUAN UMUR RENCANA JALAN PADA TAHUN KE 3 TERHADAP PENURUNAN KINERJA JALAN - Adzuha - Desmi (UNIVERSITAS MALIKUSSALEH, 2020)
AbstractHighway is a land transportation infrastructure that forms a transportation network to connect an area to other regions, so that the wheels of the economy and development can rotate well. This research was based on the road age of the third year of the road Krueng Geukueh - Beureughang, so the researchers wanted to know what factors were the causes of performance degradation on the road and the relationship between the decline in road performance on the material used. In this study includes 3 stages, namely, Core drill, Marshall Test testing and testing of Test Extracts that have been achieved using 8 (Eight) samples. So it can be concluded that there has been a decrease in asphalt levels on the road resulting in damage and decreased performance on the road. Coupled with increased charges within 3 (three) years, therefore repairs to the road are needed. From this research, it is expected to be able to provide input to improve the quality of the material and the layer of road surface pavement. Keywords : Decreasing Road Performance, Core Drill, Marshall Test, Test Extract, Asphalt Level.